Digitalization sparks a quiet revolution. Issue 5 (May 2017) - Davis, Steve; Brodersen, Sönke; Böhmer, Gero; Siemens, AG
Abstract : The pump industry mantra has always been about high production values while keeping costs and waste low, but digitalization takes that a step further. Here, we look at the major strides some of the world's biggest manufacturers are taking and the game-changing impact that is having.